The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1089/biores.2012.0229
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Ability of Freshly Generated and Cryopreserved Dendritic Cell Vaccines to Inhibit Growth of Breast Cancer in a Mouse Model

Abstract: Repetitive vaccinations with dendritic cell (DC)-based vaccines over long periods of time can break pre-existing tolerance to tumors and achieve clinically relevant immune response. This requires a large number of DCs to be generated under good manufacturing protocol, which is time- and cost intensive. Thus, producing a large numbers of DCs at one time point and cryopreserving these cells in ready-for-use aliquots for clinical application may overcome this constraint. This could also reduce batch-to-batch vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…To date, several studies have reported the effect of cryopreservation on antigen-loaded or unloaded matured DCs with results showing that the freezing and thawing process does not interfere with their phenotype in vitro as well as the trafficking and functional properties in vivo 1117. However, in contrast to the validate and consistent findings in cryopreserved mature DCs, systematical investigations on the cellular changes and the in vivo functional properties of frozen immature DC as well as its mature counterpart are very limited, and some in vitro findings are controversial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, several studies have reported the effect of cryopreservation on antigen-loaded or unloaded matured DCs with results showing that the freezing and thawing process does not interfere with their phenotype in vitro as well as the trafficking and functional properties in vivo 1117. However, in contrast to the validate and consistent findings in cryopreserved mature DCs, systematical investigations on the cellular changes and the in vivo functional properties of frozen immature DC as well as its mature counterpart are very limited, and some in vitro findings are controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the properties of cells that have experienced freezing-thawing cycle need to be fully addressed. Several studies in the early 2000s and recent years have described the effect of cryopreservation on the biology and function of DCs in vitro or in vivo , however, some conclusions are controversial10111213 and most importantly, up to now, there is still a lack of confirming evidence on whether cryopreservation would have an effect on DCs’ homing capacity.…”
mentioning
confidence: 99%
“…This finding is a little different from those of studies that used a more common breast tumor model. 48 50 This study used Swiss and mammary tumor 4T1 cell lines to develop a breast tumor model. The 4T1 cell line comes from BALB/c mice, whereas the Swiss mice retained the complete immune system.…”
Section: Discussionmentioning
confidence: 99%
“…The use of cryopreserved tolDC has been elucidated as a solution since one leukapheresis provides enough monocytes to produce large number of tolDC, which can be cryopreserved in ready-to-use aliquots. In this sense, Radhakrishnan and co-workers reported that cryopreserved DC vaccines retained in vitro and in vivo therapeutic efficacy to inhibit breast cancer growth in mice [ 10 ]. However, the process to obtain tolDC is most difficult and may be susceptible to the cryopreservation process.…”
Section: Introductionmentioning
confidence: 99%